Online Event Recognition from Moving Vehicles: Application Paper. Issue 5 (September 2019) - TSILIONIS, EFTHIMIS; KOUTROUMANIS, NIKOLAOS; NIKITOPOULOS, PANAGIOTIS; DOULKERIDIS, CHRISTOS; ARTIKIS, ALEXANDER
Abstract: We present a system for online composite event recognition over streaming positions of commercial vehicles. Our system employs a data enrichment module, augmenting the mobility data with external information, such as weather data and proximity to points of interest. In addition, the composite event recognition module, based on a highly optimised logic programming implementation of the Event Calculus, consumes the enriched data and identifies activities that are beneficial in fleet management applications. We evaluate our system on large, real-world data from commercial vehicles, and illustrate its efficiency.